Social protection legislative frameworks in South Asia from a children's rights perspective - Luca Lazzarini (International Policy Centre for Inclusive Growth (IPC-IG), 2020)
An important element of social protection systems are regulatory frameworks. The absence of a legal framework for social protection leaves individuals and communities in need exposed to arbitrary decision-making and political change. A strong statutory basis which recognises social protection as a right ensures accountable institutions and enables individuals to make legitimate claims and enforce their rights, thus creating legal awareness, which is central to the legal empowerment of the most vulnerable members of society. This Research Report assesses the state of children's right to social protection by analysing the legal frameworks supporting national social protection systems.
Keywords: 330; social protection; legal frameworks; children's rights